The Influence of The Geopolitical Situation on The Change in the Development Direction of The Port on The Example of The Ustka Seaport - Dariusz KLOSKOWSKI (Communications of International Proceedings, 2025)
The article is an attempt to show changes in the direction of perception and implementation of the development strategy of the seaport using the example of Ustka, located on the coast of the Southern Baltic Sea in Poland. In addition to the obvious changes in the strategy of the Ustka port itself related to the construction of a service base for an offshore wind farm, it is important to present another point of view, namely maritime security resulting from the state security strategy on the one hand and an important element in the implementation of energy solutions and also referring to changes in the visualization of the port resulting from the geopolitical situation of the Baltic Sea basin on the other. The main objective of the article is to analyze the current development direction of the port, including the development possibilities of the Ustka port, as one of the largest seaports located on the Central Coast of Poland. In particular, the aim of the study is to show the impact of the geopolitical situation as a potential variable influencing the change in the direction of the current development strategy of the leading seaport of the Central Coast of Poland. The research problem in the article is specified in the form of a question: Does the current geopolitical situation resulting from the armed conflict in Ukraine affect the change in the direction of the seaport development strategy? The research hypothesis of the study was specified in the form of a statement that: the location of a seaport in the vicinity of military units has a significant impact on the development of port infrastructure and superstructure, guaranteeing an increase in the advantage of the transshipment function in the port. The study used research methods and tools focused on the secondary analysis of literature sources and statistical data, as well as the use of the case study method for the Ustka port, which allowed for the analysis of the functional features of the port and the assessment of its infrastructure and infrastructure availability. The final conclusions and discussion contained in the study are focused on the answer related to the impact of the geopolitical situation, including the ongoing war in Ukraine, on the direction of changes in the port, which had a completely different strategy and development direction.
Keywords: seaport; port development strategy; geopolitical situation